Disparities in NOSE Scores and Surgical Approaches among Patients Undergoing Functional Rhinoplasty - Rozanski, Collin; Gray, Mingyang; Rousso, Joseph J.; Hirsch, Matthew B.; Rosenberg, Joshua D. (Facial Plastic Surgery, 2019)
Social determinants of health have been widely studied throughout medicine; however, their role relating to functional rhinoplasty has not been previously evaluated. The records of 178 patients who underwent functional rhinoplasty in a single health network from 2013 to 2016 were reviewed. The Nasal Obstruction Symptom Evaluation (NOSE) score was used to assess patient-reported symptoms, and patients with both preoperative and postoperative NOSE scores were included in this study. Basic demographics and surgical techniques were also collected. Differences between NOSE scores and surgical approaches to functional rhinoplasty on the basis of insurance type were measured. One hundred and sixteen patients were included for analysis, the mean age was 34.7 years (standard deviation [SD] = 16.2) and 57 (49.1%) were female. Twenty-one (18.1%) patients had public insurance and, of these, 18 patients had Medicaid. Patients (mean, SD) with Medicaid insurance (56.39, 15.6) had a slightly greater improvement in NOSE scores compared with patients with non-Medicaid insurance (47.90, 25.6) (p = 0.067). There was no statistically significant difference in preoperative NOSE scores or postoperative improvement in NOSE scores between patients with different health insurance. Furthermore, there was no statistically significant difference in surgical approaches. The majority of patients receiving functional rhinoplasty had private insurance. Medicaid patients trended toward a greater NOSE score improvement after functional rhinoplasty, but also had a closer association with a history of nasal trauma and prior surgery. Future study is needed to better understand the association between socioeconomic status and disparities in care. Understanding how social determinants of health affect patients may reveal potential inherent biases, improve delivery of care, and translate to better patient outcomes.
Keywords: rhinoplasty; social determinants of health; functional rhinoplasty; NOSE score; NOSE